Hybrid fluid–kinetic neutral model based on a kinetic correction on a fluid solution. Issue 6 (2nd March 2018) - Horsten, N.; Samaey, G.; Baelmans, M.
Abstract : We describe a hybrid fluid–kinetic approach for the neutral particles in the plasma edge for a simplified 1D model. This is done by means of a micro–macro decomposition of the kinetic equation. The closure terms from the fluid (macro) equations are modelled with a Monte Carlo (MC) simulation of the kinetic (micro) equation. We assess two hybrid neutral models with different underlying fluid models: (a) a pure pressure diffusion equation and (b) a pressure diffusion equation superposed with an energy equation. Both hybrid models reduce the statistical errors on the resulting particle and momentum sources by about a factor five for a given computational time, whereas the statistical error on the energy source is reduced by about a factor three compared to the full kinetic MC simulation. The hybrid model without the fluid energy equation slightly outperforms the model with the energy equation for the prediction of the particle and momentum sources, but adding an energy equation to the fluid model is beneficial for reducing the statistical error on the energy source.